ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI PROGRESSIVE MUSCLE RELAXATION TERHADAP TINGKAT FATIGUE PADA PASIEN YANG MENJALANI HEMODIALISA DI RSPAD GATOT SOEBROTO - Amalia Tiara Kusuma (2023)
Chronic Kidney Failure is defined as a clinical condition that results in changes in kidney function or structure and is irreversible and can develop progressively which can result in metabolic wastes converging to cause electrolyte, water and acid-base balance disorders. The most common treatment for chronic kidney disease to replace kidney function is hemodialysis. Fatigue is one of the most common stressors reported by many patients undergoing hemodialysis. To reduce the level of fatigue, patients are given interventions in accordance with evidence base nursing, namely progressive muscle relaxation therapy or progressive muscle relaxation therapy during the dialysis process. The intervention is given for 3x a week or according to the hemodialysis schedule for 10-15 minutes. Before the intervention of progressive muscle relaxation therapy, the patient was given a Fatigue Assessment Scale (FAS) questionnaire to measure the level of fatigue. The results obtained were that the total FAS value before intervention was 40 in managed patients while in resume patients the total FAS value was 23. After the intervention, the patient was re-evaluated to measure the level of fatigue by giving the FAS questionnaire. The results of the FAS questionnaire after the intervention were found that the total FAS value decreased by 20 in managed patients and 17 in resume patients. So, it can be concluded that progressive muscle relaxation therapy can be trusted and effective for reducing fatigue levels.